Face specific inversion effects provide evidence for two subtypes of developmental prosopagnosia. (9th September 2022) - Bennetts, Rachel J.; Gregory, Nicola J.; Tree, Jeremy; Di Bernardi Luft, Caroline; Banissy, Michael J.; Murray, Ebony; Penton, Tegan; Bate, Sarah
Abstract: Many studies have attempted to identify the perceptual underpinnings of developmental prosopagnosia (DP). The majority have focused on whether holistic and configural processing mechanisms are impaired in DP. However, previous work suggests that there is substantial heterogeneity in holistic and configural processing within the DP population; further, there is disagreement as to whether any deficits are face-specific or reflect a broader perceptual deficit. This study used a data-driven approach to examine whether there are systematic patterns of variability in DP that reflect different underpinning perceptual deficits. A group of individuals with DP (N = 37) completed a cognitive battery measuring holistic/configural and featural processing in faces and non-face objects. A two-stage cluster analysis on data from the Cambridge Face Perception Test identified two subgroups of DPs. Across several tasks, the first subgroup (N = 21) showed typical patterns of holistic/configural processing (measured via inversion effects); the second (N = 16) was characterised by reduced or abolished inversion effects compared to age-matched control participants (N = 91). The subgroups did not differ on tasks measuring upright face matching, object matching, non-face holistic processing, or composite effects. These findings indicate two separable pathways to face recognition impairment, one characterised by impaired configural processing and the other potentially by impaired featural processing. Comparisons to control participants provide some preliminary evidence that the deficit in featural processing may extend to some non-face stimuli. Our results demonstrate the utility of examining both the variability between and consistency across individuals with DP as a means of illuminating our understanding of face recognition in typical and atypical populations. Highlights: Face specific inversion effects provide evidence for two subtypes of developmental prosopagnosia. Cluster analyses revealed two groups of individuals with developmental prosopagnosia. Some people might struggle with faces because of a deficit in holistic processing. Others may struggle with faces because of a deficit in processing local features. These findings suggest partially separable routes to face recognition deficits.